MODEL OF INTEGRAL KEY COMPETENCE OF FUTURE QUALIFIED WORKERS OF SEWING PROFILE - Halyna Оdnoroh (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article raises the issue of the lack of a list of current key competencies required by the modern labor market of the garment industry in the State Standards of Vocational Education for the professions «Tailor» and «Cutter». The author analyzes the legislative and regulatory documents related to the topic of key competences of future skilled workers in the sewing profile; compared the results of the study of the labor market of the garment industry on the demand for key competences. The actual abilities of future tailors and cutters, which are necessary for their professional success, increase of competitiveness, formation of professional mobility and adaptation in the labor market of the garment industry, are determined. It is emphasized that creativity in the context of garment production is the basis for the development of many key competences of future garment professionals. The expediency of introducing the definition of «integral key competence of future skilled sewing workers» is substantiated. The definition of integral key competence of future skilled workers of a sewing profile is given and its structure consisting of value-motivational, cognitive-activity and personal-reflexive components is defined. Each of these three components in the future act as criteria for the development of the phenomenon under study. The author designed a model of integrated key competence of future skilled sewing workers, which reflects the relationship and interdependence of all its components, which structure the current abilities of future professionals in this field.